Reconstructing the chronology of the natural and anthropogenic uranium isotopic signals in a marine sediment core from Beppu Bay, Japan. Issue 4 (April 2023) - Takahashi, Hodaka; Sakaguchi, Aya; Hain, Karin; Wiederin, Andreas; Kuwae, Michinobu; Steier, Peter; Takaku, Yuichi; Yamasaki, Shinya; Sueki, Keisuke
Abstract: The long-lived U isotopes, 233 U and 236 U, have been used increasingly in recent years as marine circulation tracers and for identifying sources of uranium contamination in the environment. The sedimentation histories of these two U isotopes in combination with natural 238 U were reconstructed for an anoxic sediment core collected from Beppu Bay, Japan, in the western North Pacific Ocean showing good time resolution (less than 2.6 y/sample). The 233 U/ 236 U atom ratio showed a prominent peak of (3.20 ± 0.30) × 10 −2 around 1957 which can be attributed to the input from atmospheric nuclear weapons tests including thermonuclear tests conducting in the Equatorial Pacific. The integrated 233 U/ 236 U ratio of (1.64 ± 0.08) × 10 −2 for the sediment was found to be in relatively good agreement with the representative ratio published for global fallout (∼1.4 × 10 −2 ). A prominent increase in the authigenic ratio of 233 U/ 238 Ua, s in the leached fraction (1.39 ± 0.11 × 10 −11 ) and the bulk digestion (1.36 ± 0.10 × 10 −11 ) was also observed around 1957. This reflects the input supply of 233 U to the seawater which is known to have a relatively constant 238 U content. The authigenic 236 U/ 238 Ua, s ratio (0.18 ± 0.02 × 10 −9 ) obtained for 1921 increased from the early 1950's to a maximum of (6.59 ± 0.60) × 10 −9 around 1962. The variation in this ratio represents well the introduction history of U into the surface environment without site-specific U contamination and the time profile is also consistent with the 137 Cs signature. This work thus provides a benchmark for the long-term use of the isotopic U composition as an input parameter for seawater circulation tracers and as a chronological marker for anoxic sediments and sedimentary rocks. Especially the 233 U/ 236 U ratio may serve as a key-marker for the new geological age Anthropocene.